(untitled) (Revista de História Regional, 2023)
Based on the perspective of global environmental history, it is evident that through the municipality of Palmas/PR, fundamental means were formed for the environmental devastation of the Araucaria Forest, in the southwest region of Paraná, practiced from the 1950s onwards. 1935, the timber sector began to move from União da Vitória/PR and surroundings, the epicenter of the FOM devastation in the period, to Palmas and towards the southwest, with political and economic support coming from the state capital. The analyzes allowed the perception that between the years 1935 and 1955 the first sawmills were installed and regularized in Palmas and that roads were created so that undertakings of this kind and colonization could advance over the southwest. Although most of the migrants from the states of Santa Catarina and Rio Grande do Sul who settled in the southwest in the first half of the 20th century with the aim of developing agricultural activities arrived in the region by other routes, there were no means to dispose of their productions and the structuring of roads in Palmas facilitated the transport of wood and agricultural products.